OPTIMALISASI MODEL PENGEMBANGAN WAKAF TUNAI DI INDONESIA - Ananto, Tri (Taksasila Edukasi Insani, 2025)
This research aims to find an optimum point for cash waqf development in Indonesia. It is a literature study using content analysis to provide an alternative scientific study of cash waqf in Indonesia. This study discusses a feasible alternative model for optimizing cash waqf development through a production function approach. It concludes that optimizing waqf with a production approach is greatly influenced by Nadzhir's professionalism. Nadzir's professionalism occurs when there is a breakthrough in many aspects and needs to be facilitated by the government. One of the ways is establishing an education program for cash waqf management at Sekolah Tinggi Akuntansi Negara (STAN), where the graduates become certified professional nadzir and employees under the Ministry of Finance of the Republic of Indonesia. This breakthrough will optimize cash waqf and positively impact the development of Indonesia and the Muslim community. Keywords : Waqf, Cash Waqf, Development Model